De la caridad a la acción social. Las Conferencias de San Vicente de Paul en el arzobispado de Michoacán (1900-1911) (Tzintzun, Revista de Estudios Históricos, 2019)
The study deals with the rise, importance and development of the Catholic organization called Conferences of San Vicente de Paul in the Archdiocese of Michoacán, promoted by Archbishop Atenógenes Silva at the end of the Porfiriato. This organization had a key representation for the ratification and increase of the social influence of the Church at the parish level and that in the end permeated the political thought of social Catholicism.